Group consensus peer review in radiation oncology: commitment to quality - W Neil Duggar (Radiation Oncology, 2018)
Abstract Background Peer review, especially prospective peer review, has been supported by professional organizations as an important element in optimal Radiation Oncology practice based on its demonstration of efficacy at detecting and preventing errors prior to patient treatment. Implementation of peer review is not without barriers, but solutions do exist to mitigate or eliminate some of those barriers. Methods Peer review practice at our institution involves three key elements: new patient conference, treatment planning conference, and chart rounds. The treatment planning conference is an adaptation of the group consensus peer review model from radiology which utilizes a group of peers reviewing each treatment plan prior to implementation. The peer group in radiation oncology includes Radiation Oncologists, Physician Residents, Medical Physicists, Dosimetrists, and Therapists. Thus, technical and clinical aspects of each plan are evaluated simultaneously. Results Though peer review is held in high regard in Radiation Oncology, many barriers commonly exist preventing optimal implementation such as time intensiveness, repetition, and distraction from clinic time with patients. Through the use of automated review tools and commitment by individuals and administration in regards to staffing, scheduling, and responsibilities, these barriers have been mitigated to implement this Group Consensus Peer Review model into a Radiation Oncology Clinic. Conclusion A Group Consensus Peer Review model has been implemented with strategies to address common barriers to effective and efficient peer review.